T Cells and Gene Regulation: The Switching On and Turning Up of Genes after T Cell Receptor Stimulation in CD8 T Cells - Conley, James M.; Gallagher, Michael P.; Berg, Leslie J. (Frontiers in Immunology, 2016)
Signaling downstream of the T cell receptor (TCR) is directly regulated by the dose and affinity of peptide antigen. The strength of TCR signaling drives a multitude of T cell functions from development to differentiation. CD8 T cells differentiate into a diverse pool of effector and memory cells after activation, a process that is critical for pathogen clearance and is highly regulated by TCR signal strength. T cells rapidly alter their gene expression upon activation. Multiple signaling pathways downstream of the TCR activate transcription factors, which are critical for this process. The dynamics between proximal TCR signaling, transcription factor activation, and CD8 T cell function are discussed here. We propose that Inducible T cell kinase (ITK) acts as a rheostat for gene expression. This unique regulation of TCR signaling by ITK provides a possible signaling mechanism for the promotion of a diverse T cell repertoire in response to pathogen.